The effect of political will, information technology, and the quality of financial reporting information on fraud prevention - Haliah; Hasnawiya Hasan; Syamsuddin; Fatmawati; Andi Ratna Sari Dewi; Muhammad Alief Fahdal Imran Oemar; Linda Arisanty Razak (Public and Municipal Finance)
This study aims to analyze the effect of political will and information technology on fraud prevention either directly or through the quality of financial reporting information. This study uses a survey method that intentionally targets five village officials responsible for village financial administration. The survey was conducted in Pangkep Regency, South Sulawesi Province, Indonesia. Data collection was carried out using a questionnaire with a total research sample of 325 respondents. Data analysis was conducted using partial least squares structural equation modeling with the help of the SmartPls 4.0 application. The results showed that political will had a positive and significant effect on fraud prevention (β = 0.198; t-value = 3.230 > 1.97) but had no effect on the quality of financial reporting information (β = 0.053; t-value = 0.696 < 1.97). Information technology had a significant negative effect on fraud prevention (β = –0.198; t-value = 3.019 > 1.97) and a significant positive effect on the quality of financial reporting information (β = 0.186; t-value = 2. 863 > 1.97). Fraud prevention has a positive and significant effect on the quality of financial reporting information (β = 0.161; t-value = 2.598 > 1.97). Political will has no significant effect on fraud prevention through the quality of financial reporting information (β = 0.009; t-value = 0.628 < 1.97), while information technology has a positive and significant effect on fraud prevention through the quality of financial reporting information (β = 0.029; t-value = 2.093 > 1.97).